The views of students of the upper basic stage in public schools about distance learning via educational platforms during the Corona pandemic through: A case study based on graphics analysis - Alimat, Fatima Mustafa (Journal of Educational and Psychological Sciences, 2021)
This research aimed at studying the views of students of the upper basic stage in public schools about distance learning via educational platforms during the Corona pandemic through a case study based on graphics analysis. One of the qualitative research methods was used, which is the case study, the case study in this research was based on the analysis of graphics, and the research sample consisted of 8 students (7 females and one male) studying in the eighth, ninth and tenth grades from 3 public schools that include the upper basic stage in Mafraq Governorate. The research tools also included a case study through drawing to reveal the mental methods of individuals against facts and events, and the research reached three main conclusions. First: that students in the eighth, ninth, and tenth grades of upper basic schools rely to a large extent on laptops to use educational platforms during the Corona pandemic. Second: The method of educational platforms in presenting information does not answer the inquiries of some students, so it does not replace face-to-face learning. Third: The graphics showed that the frequent use of these technologies by the student and the teacher led to health problems for them, such as visual fatigue. Accordingly, the researcher made recommendations to those in charge of educational platforms represented in the need to simplify and facilitate the scientific concepts presented on educational platforms using interesting methods such as puppet theater and cartoon films that present the subject in a simplified manner, and the need to integrate face-to-face and distance education, and recommendations for school administrations represented by targeted awareness campaigns For parents to reduce their behaviors that led their children to neglect and dependence on parents during the distance learning period, and recommendations to parents about the need to instill a sense of security in the hearts of their children, and increase the care and love provided to them, especially in this critical age stage (adolescence), and the presence of an individual with patience and positivity In the family and has a close relationship with the student, he helps him review the book’s information after attending lessons on educational platforms and other knowledge channels.